Pelatihan Media Pembelajaran Berbasis Augmented Reality Dalam Peningkatan Keterampilan Guru Di Era Digital - Erina Ratnaning Tiastuti; Endang Sri Maruti; Sesaria Prima Yudhaningtyas (CV. Multi Kreasi Media, 2023)
Rapid progress in the world of education is influenced by technological developments so that it has an impact on the utilization of technology as a learning medium in the digital era. One of the digital learning media that is currently in demand is Augmented Reality (AR) based learning media using the Assemblr Edu Website. However, teachers at SDN Nguntoronadi 2 do not have the skills or abilities of Augmented Reality (AR) technology so they cannot create Augmented Reality-based learning media using the Assemblr Edu Website. Therefore, it is necessary to hold training to create Augmented Reality (AR) based learning media in improving teacher skills in the digital era using the Assemblr Edu Website. This community service activity aims to make teachers understand Augmented Reality (AR) technology, understand how to use and have the skills to make Augmented Reality (AR) based learning media using the Assemblr Edu Website. This community service activity uses a monological and dialogical approach. The participants who participated in this community service activity were 10 teachers at SDN Nguntoronadi 2. After the training, 90% of teachers have understood about Augmented Reality (AR) and how to use the Assemblr Edu Website and are able to create Augmented Reality (AR) based learning media using the website.